Reduction of the Local Stress Field around Holes through Porous Shaped Structures - Stefano Monti (Communications - Scientific letters of the University of Zilina, 2018)
Geometrical discontinuities in mechanical components are detrimental for the mechanical properties of the product itself. Actually, in proximity of such features, the stress increases due to the stress concentration factor, that in the case of a circular hole is equal to 3. Several solutions have been proposed to reduce the stress concentration value. In the present article, the application of a particular porous pattern that can be obtained by laser cutting with the appropriate finishing requirements is introduced in order to modify the local stress field and reduce the stress concentration value near the hole boundary.